2021
DOI: 10.4314/ijbcs.v14i9.9
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the ethnobotanical inventory of medicinal plants used for the treatment of typhoid fever in Adamaoua region, Cameroon

Abstract: Since ancient Greek-Roman times, the use of plants to cure many human diseases is still common. The present ethnobotanical survey was conducted to contribute to the knowledge of medicinal plants used for the treatment of typhoid fever in three sub divisions of Vina division, Adamawa Cameroon. After having explained the importance of this study to interviewees, 41 traditional healers have agreed and delivered information regarding the medicinal plants they use as well as the different preparation and administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
0
0
1
Order By: Relevance
“…Un des critères de choix les plus importants pour la sélection est la preuve de la sécurité d'emploi à travers des preuves d'innocuité et d'efficacité. En effet, à partir des enquêtes ethnobotaniques, des informations sur l'utilisation des plantes médicinales par des tradipraticiens et les populations sont rassemblées (Chegaing et al, 2020). Sur la base de ces informations, des études ethnopharmacologiques in vitro, ex vivo et in vivo (chimie, pharmacologie, toxicologie, microbiologie, etc.)…”
Section: Critères De Sélection Des Plantes Médicinalesunclassified
“…Un des critères de choix les plus importants pour la sélection est la preuve de la sécurité d'emploi à travers des preuves d'innocuité et d'efficacité. En effet, à partir des enquêtes ethnobotaniques, des informations sur l'utilisation des plantes médicinales par des tradipraticiens et les populations sont rassemblées (Chegaing et al, 2020). Sur la base de ces informations, des études ethnopharmacologiques in vitro, ex vivo et in vivo (chimie, pharmacologie, toxicologie, microbiologie, etc.)…”
Section: Critères De Sélection Des Plantes Médicinalesunclassified
“…Numerous plants have been assessed for their therapeutic potential in treating various ailments around the world for centuries, encompassing both historical practices and contemporary cultures. The evaluation extends not only to their medicinal properties but also to their diverse applications and uses (Nana et al, 2023;Fodouop et al, 2020;Ballo et al, 2020). Henna has been valued for centuries for its medicinal properties, as it contains a variety of phytochemicals that contribute to its therapeutic effects (Pasandi Poor et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…and Nguyen et al (2019), the most used medicinal plants for treatment of typhoid fever and gastrointestinal disorders were species from the Cactaceae family. Different published reports have revealed that leaves of medicinal plant could be employed for prevention of gastrointestinal disorders(Chegaing et al, 2020;Dey & De, 2012;Nguyen et al, 2019). Another study was carried out by Ozgun-Acar et al (2022).…”
mentioning
confidence: 99%